Integrating low-intensity plyometrics into strength and conditioning programs - Shiner, J.; Bishop, T.; Cosgarea, A. J. (Strength and Conditioning Journal, 2005)
This article will define plyometrics and provide a basis of understanding for functional progressions leading up to plyometric exercises. Readiness for plyometrics is presented as a method of defining an adequate strength base. Sample exercises and progressions are provided, including an example of the integration of low-intensity plyometrics into a speed development program.